(untitled) (Vietnam Journal of Community Medicine, 2022)
Objective: In developing countries, pneumococcal pneumonia is the common cause of death in children. Pneumococcal pneumonia can be severe and may need to be treated at specialized hospital, like Central Children’s Hospital. The purpose of this research is to describe clinical and paraclinical characteristics of pneumococcal pneumonia in Viet Nam Central Children’s Hospital. Methods: A prospective cohort study involving 169 children aged 1-month to 15-years admitted to Viet Nam Central Children’s Hospital from September 2015 to December 2018. Results: S. pneumoniae accounts for 41,52% of pneumonia cases in children, with the male and female ratio of 2/1, occurring most frequently at children ages 2-months to 2-years. Clinical manifestations are broad and nonspecific. The most common clinical symptoms are cough (94,67%), fever (89,94%), runny nose (88,76%), wheeze (78,11%), cyanosis (12,43%), coarse (80,47%) and chest retraction (62,7%). The incidence of leukocytosis, high CRP and anemia was 91,72%, 68,05% and 40,24%, respectively. The most common finding in chest X-ray was broncho-alveolar (79,29%), lobar or segmental consolidation (17,16%) and pleural fluid (5,33%), pneumococcal severe pneumonia (68%). Conclusion: Pneumococcus is currently the leading cause of pneumonia in children. Clinical manifestations of pneumococcal pneumonia in children are nonspecific. Lesions on X-ray are mainly broncho-alveolar, which is different from previous studies, mostly lobar or segmental consolidation. The incidence of pneumococcal severe pneumonia is high, so it is necessary to develop the methods of diagnosis for early detection to limit the complications of the disease.